2021
DOI: 10.1001/jamaneurol.2021.0001
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy for Primary Distal Posterior Cerebral Artery Occlusion Stroke

Abstract: IMPORTANCE Clinical evidence of the potential treatment benefit of mechanical thrombectomy for posterior circulation distal, medium vessel occlusion (DMVO) is sparse.OBJECTIVE To investigate the frequency as well as the clinical and safety outcomes of mechanical thrombectomy for isolated posterior circulation DMVO stroke and to compare them with the outcomes of standard medical treatment with or without intravenous thrombolysis (IVT) in daily clinical practice. DESIGN, SETTING, AND PARTICIPANTSThis multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 47 publications
12
125
2
Order By: Relevance
“…Most recently, a retrospective multicenter study reported findings comparing EVT and BMM with or without thrombolysis in patients with peripheral PCAO, i.e., P2–P4 segments, hence after exclusion of P1 occlusions ( 13 ). Consistent with the more peripheral location, the median NIHSS of five was even lower than in the present study and the aforementioned by Strambo et al ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a retrospective multicenter study reported findings comparing EVT and BMM with or without thrombolysis in patients with peripheral PCAO, i.e., P2–P4 segments, hence after exclusion of P1 occlusions ( 13 ). Consistent with the more peripheral location, the median NIHSS of five was even lower than in the present study and the aforementioned by Strambo et al ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary efficacy endpoint was early neurological improvement (ENI) defined as a decrease in four or more points compared to baseline NIHSS or zero points on the earliest NIHSS score after 24 h but before discharge in accordance with a recently published study ( 13 ). The secondary endpoint was good outcome, defined as mRS 0–2 after 90 days.…”
Section: Methodsmentioning
confidence: 99%
“…Medium vessel occlusions (MeVOs) defined as M2/3, A2/3, and P2/3 segment occlusions naturally represent the next frontier [92]. Compared with standard medical treatment with or without intravenous thrombolysis, mechanical thrombectomy for posterior circulation is also a safe and technically feasible treatment option for occlusions of the P2 or P3 segment of the posterior cerebral arteries if performed at comprehensive stroke centers [93].…”
Section: Inclusion Criteria and Techniques Of The Treatmentmentioning
confidence: 99%
“…21 The same applies to the validity of the NIHSS in PCA strokes: P2/P3 occlusions often present with lower NIHSS scores, possibly because the NIHSS does not optimally reflect the typical posterior circulation stroke symptoms. 10 Therefore, we included detailed descriptions of the neurological loss of function for each case scenario, rather than only an NIHSS value (see online supplemental figures 1-3).…”
Section: Ischemic Strokementioning
confidence: 99%
“…5 Given the overwhelming efficacy of EVT in LVO stroke 6 and encouraging preliminary safety and efficacy data in the MeVO patient population, 7 physicians are increasingly treating MeVO patients with EVT. [8][9][10] A well-designed clinical trial to evaluate EVT in MeVO stroke is needed, but a logistical concern for such a trial includes understanding which factors may influence clinical equipoise for EVT. In this case-based survey study, we aimed to measure the degree of influence prior intravenous alteplase treatment would have on physicians' EVT decision-making in MeVO stroke.…”
Section: Introductionmentioning
confidence: 99%